Role of neuropeptide FF in central cardiovascular and neuroendocrine regulation - Jhamandas, Jack H.; Goncharuk, Valeri (Frontiers in Endocrinology, 2013)
Neuropeptide FF (NPFF) is an octapeptide belonging to the RFamide family of peptides that have been implicated in a wide variety of physiological functions in the brain including central cardiovascular and neuroendocrine regulation. The effects of these peptides are mediated via NPFF1and NPFF2 receptors that are abundantly expressed in the rat and human brain. Herein, we review evidence for the role of NPFF in central regulation of blood pressure particularly within the brainstem and the hypothalamic paraventricular nucleus (PVN). At a cellular level, NPFF demonstrates distinct responses in magnocellular and parvocellular neurons of the PVN, which regulate the secretion of neurohypohyseal hormones, and sympathetic ouflow, respectively. Finally, the presence of NPFF system in the human brain and its alterations within the hypertensive brain are discussed.